2020
DOI: 10.1096/fba.2019-00070
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of STAT3 pathway ameliorates acute liver injury in vivo via inactivation of inflammatory macrophages and hepatic stellate cells

Abstract: Abbreviations: AEC, 3-amino-9-ethyl carbazole; Arg1, Arginase 1; CCL2/MCP1, chemokine (C-C motif) ligand 2/Macrophage chemotactic protein-1; CCl 4 , carbon tetrachloride; CCR2, chemokine (C-C motif) receptor 2; DAPI, 4',6-diamidino-2-phenylindole; DMSO, Dimethyl sulfoxide; ECM, extracellular matrix; HRP, horseradish peroxidase; HSCs, hepatic stellate cells; IL-1β, Interleukin 1 beta; IL-6, Interleukin 6; MHC II, major histocompatibility complex class II; MRC1, mannose receptor 1; mRNA, messenger RNAs; NaCl, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“… 10 WP1066, another STAT3 inhibitor, significantly reduced the level of TNF-α and IL-6 in LPS- or IFN-γ-stimulated mouse RAW264.7 macrophages. 11 In vivo , STAT3 inhibitor Nifuroxazide significantly decreased the mRNA and protein level of TNF-α and IL-18 and reduced infiltration of inflammatory cells in diabetes-associated renal injury. 23 LLL12, an allosteric STAT3 inhibitor, also attenuated the infiltration of inflammatory cells and the level of TNF-α and IL-1β in LPS-induced acute lung injury.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 10 WP1066, another STAT3 inhibitor, significantly reduced the level of TNF-α and IL-6 in LPS- or IFN-γ-stimulated mouse RAW264.7 macrophages. 11 In vivo , STAT3 inhibitor Nifuroxazide significantly decreased the mRNA and protein level of TNF-α and IL-18 and reduced infiltration of inflammatory cells in diabetes-associated renal injury. 23 LLL12, an allosteric STAT3 inhibitor, also attenuated the infiltration of inflammatory cells and the level of TNF-α and IL-1β in LPS-induced acute lung injury.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, increasing evidence indicates that STAT3 plays crucial roles in the regulation of inflammation and apoptosis. 10 , 13 STAT3 has become a novel therapeutic target for intervention in inflammation-related disorders, 10 , 11 but it remains unclear whether STAT3 plays a part in acute hepatic damage. In the present study, the results showed that Stattic mitigated the hepatic morphologic abnormalities, such as hepatocellular necrosis and destruction of hepatic lobule, and decreased the level of aminotransferase in LPS/ D -GalN-insulted mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 contributes to brosis by inducing the production of ECM, generally sustaining the differentiation of organ resident cells via canonical and non-canonical pathways. Indeed, several lines of evidence report the fundamental role of STAT3 in broblast plasticity in different tissues [6,18], where the inhibition of its signaling pathway attenuates brosis by decreasing several markers, among which α-SMA [34] and N-cadherin [27]. Since S100A4 is a known inducer of JAK/STAT pathway, it is possible that S100A4 knock-down can indirectly decrease the levels of the brotic molecules α-SMA and N-cadherin through the inhibition of STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Such multidirectional participation highlights the complexity of parallel processes and their insufficient investigation. STAT3 regulates a number of fundamental cellular processes, including inflammation, proliferation, differentiation, and cell migration [ 142 ]. STAT3 can also regulate apoptosis by inducing the expression of the apoptosis inhibitor Bcl-2 (B-cell lymphoma 2) [ 143 , 144 ].…”
Section: Participation Of Abca1 In the Regulation Of Inflammation mentioning
confidence: 99%